Effect of feeding Mentha piperita (Pudina) on nutrient balance and blood biochemical of small ruminants - Bhat, Asif Rasool; Ishfaq, Ahmad; Ganai, Abdul Majeed; Beigh, Yasir Afzal; Sheikh, Gowhar Gull (Indian Journal of Animal Nutrition, 2019)
The study was taken to evaluate the effects of Mentha piperita(Pudina),a herbal feed additive, on the nutrient balance and blood biochemical in sheep.Ten male adult Bakerwal sheep were divided in to control (T0) and treatment (T1) groups. The complete ration for T1was fortified with herbMentha piperita@3%, level per pre-determined by in vitrodigestibility experiment.DM intake, OM intake, average daily gainand digestibility coefficients of DM, OM, CP and EE showed significant (P<0.05) differences where as non-significant (P<0.05) differences were observed in digestibility coefficients of NFE, NDF, ADF and HC. Significant(P<0.05)increase in %DCP and %TDN were recorded in T1group as compared to T0group. Nitrogen, calcium and phosphorus balance were comparable between two groups and were positive in both groups. Among haemato-biochemical parameters blood glucose, Hb, PCV and total serum proteins, differed non-significantly (P≤0.05) between the groups, both before and after experimental feeding except the BUN, which was found significantly (P≤0.05) higher in herb supplemented group.